2020
DOI: 10.1111/hepr.13545
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement in portal‐systemic liver failure symptoms and successful management of portal‐splenic venous hemodynamics by the combination of interventional radiology and pharmacotherapy

Abstract: This study describes a case of hepatitis C virus-related decompensated cirrhosis with portal-systemic liver failure and refractory encephalopathy. It was successfully managed with a combination of interventional radiology and pharmacotherapy, to improve hepatic function, including hyperammonemia and to control portal-splenic venous hemodynamics with hepatic venous pressure gradient (HVPG) monitoring. A man in his late 50s presented with a Child-Pugh score of 13, Model for End-Stage Liver Disease-sodium (MELD-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A case-control study from the USA revealed that the prevalence of PoPH was significantly higher among females and patients with AIH and was numerically higher among patients with PBC. 34 Splenectomy and splenic arterial embolization 35 are well known as one of the treatments for portal hypertension, and they are often performed for complications associated with portal hypertension. Segraves et al reported a high risk of subsequent PoPH in patients with AIH and in those with a history of splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study from the USA revealed that the prevalence of PoPH was significantly higher among females and patients with AIH and was numerically higher among patients with PBC. 34 Splenectomy and splenic arterial embolization 35 are well known as one of the treatments for portal hypertension, and they are often performed for complications associated with portal hypertension. Segraves et al reported a high risk of subsequent PoPH in patients with AIH and in those with a history of splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…55 56 57 Moreover, PSE can reverse portal hypertension and hepatic dysfunction induced by balloon-occluded retrograde transvenous obliteration for hepatic encephalopathy. 58 The improvement in portal-systemic encephalopathy is likely attributed to obliteration of portal-systemic shunts followed by PSE. 59 For patients undergoing liver transplant which may be complicated by graft dysfunction or hepatitis C, 60 these therapeutic benefits of PSE persist.…”
Section: Discussionmentioning
confidence: 99%
“…Tajiri reported that cholinesterase activity and serum albumin increased ammonia levels after all therapy was carried out. 11,20,27 Long-term monitoring is carried out for up to 1 year after the procedure to assess responses such as recurrent variceal bleeding, bleeding at other sites such as gingiva or epistaxis, and the ability to respond to the planned intervention. Laboratory examination after the PSE procedure is in the form of a complete blood picture to assess the number of erythrocytes, leukocytes, and platelets, which are assessed every 2 weeks, 1 month, 6 months, and 1 year after the PSE procedure.…”
Section: Introductionmentioning
confidence: 99%